Nilai-nilai Pendidikan Karakter dalam Seloko Adat Kelurahan Sengeti - Fitriyanti, Maya; Salam, M.; Melisa, Melisa (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Introduction. The research aims to determine the values of character education in the traditional seloko of Sengeti subdistrict. The purpose of this article is to find out what character education values are contained in traditional seloko. Research methods. The research method used in this research is descriptive, namely an ethnographic study which aims to explain the values of character education in the traditional seloko of Sengeti Village. Results and Discussion. The results of this research illustrate: first, carrying out and applying various traditional seloko activities based on the Hadith and Al-Qur'an in accordance with the value of religious character education. Second, the attitude of thinking and acting in traditional seloko is based on a sense of sincerity and enthusiasm in accordance with the values of nationalist character education. Third, a responsible and trustworthy attitude in traditional seloko is in accordance with the value of independent character education. Fourth, an attitude of mutual assistance, respect and enthusiasm in accordance with the value of mutual cooperation character education. Fifth, an attitude of trustworthiness and trustworthiness is in accordance with the character education value of integrity. Conclusions and suggestions. Seloko Adat contains character education values. It is hoped that traditional institutions and the government will carry out traditional seloko training for the next generation of young people in Sengeti Village.